Observations of the serotine bat Eptesicus serotinus (Schreber, 1774) in underground hibernacula of Slovenia - Primož Presetnik; Monika Podgorelec (Natura Sloveniae)
Eptesicus serotinus is rarely found hibernating in Slovenia. This article summarises data on all 18 recorded published and new field observations. Individual bats were found in the entrance parts of 11 caves, one in a cliff overhang, and one in a cellar. Bats were mostly resting in small crevices and less frequently hanging freely from ceiling or walls. In one case, E. serotinus was also found 40 cm deep in stone gravel. Temperatures near bats ranged from just below zero to approximately +5.5°C.